Functional status strengthening in elite racing skiers at final training stage before main start of season - Golovachev, A. I.; Abramova, T. F.; Gorbunova, E. A.; Shirokova, S. V.; Sigov, E. A.; Novikova, N. B. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to identify the peculiarities of functional adaptation of elite racing skiers at the venue for the final stage of training for the main start of the season in different phases of acute acclimatization.